Identify Industrial Work Practices in the Food and Beverage Product Department of Grand Ixora Kuta Resort - Yanti, Ni Ketut Karisma; Anggayana, I Wayan Agus (Jurnal Manajemen Pelayanan Hotel, 2023)
This research Identify Industrial Work Practices in the Food and Beverage Product Department of Grand Ixora Kuta Resort. It can be used as a guide to improve the quality of work and creativity in entering the tourism industry. Increasing student knowledge in the Food and Beverage products field and implementing training will be helpful later when facing the industrial world. This research is descriptive qualitative research. The document used in this research is taken from Industrial Work Practices in the Food and Beverage Product Department of Grand Ixora Kuta Resort Students' report. After carrying out industrial work practices, the researcher gained a lot of useful work experience in the form of theories and practical knowledge regarding the Food and Beverage Product field and the ability to work together. In addition, the author has carried out one of the requirements for completing the Food and Beverage Product Study program by carrying out industrial work practices. Keywords: Industrial Work Practices, Food and Beverage Product Department, Quality of work, Tourism industry